Development and characterization of creamy mixed sweet of green coconut and pineapple (Research, Society and Development, 2021)
The solid albumen of the green coconut is a co-product of the coconut water industry that has high nutritional quality, but is widely wasted in Brazil. The aim of this study was to evaluate of using this co-product in the production of mixed coconut and pineapple sweet and to characterize them. Three formulations were prepared (F1 4.8% pineapple and coconut, F2 green coconut 50%, pineapple 24.25% and F3 green coconut 59.7% and pineapple 10%) and microbiological, physical-chemical and sensory analyzes were performed (acceptance and purchase intention). The results revealed that all formulations were safe for human consumption with counts below the detection limit (